Mobile banking : evolution or revolution? - Nicoletti, Bernardo; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Mobile is impacting heavily on our society today. In this book, Nicoletti analyzes the application of mobile to the world of financial institutions. He considers future developments and the possible use of mobile to help the transformation in products, processes, organizations and business models of financial institutions globally.
Keywords: Banks and banking, Mobile